Transformative Social Spirituality Among Santri Gobal Gabul: An Ibn Khaldunian Study Of Hidden Curriculum - Habibi, Rohim; Kusmanto, Adi; Hadziq, Abdulloh (Universitas Islam Indonesia, 2025)
This study explores the transformative construction of social spirituality within the Santri Gobal Gabul community, a community-based religious movement affiliated with Pondok Pesantren Al-Muhammad Cepu. Drawing upon Ibn Khaldun’s Sociology of Education, it examines how the hidden curriculum of the Pengajian Malam Ahad (Saturday Night Recitation) functions as a form of non-formal education that transcends conventional pedagogical frameworks. The research focuses on three key dimensions: (1) reconstructing social spirituality through Ibn Khaldun’s concept of ‘ilm al-‘umran al-insani and the development of al-malakah (internalized moral competence); (2) identifying the mechanisms of the hidden curriculum that organically foster tolerance, empathy, and interfaith inclusivity; and (3) formulating a character education model grounded in social spirituality within the pesantren tradition. Employing a qualitative descriptive approach with a phenomenological lens, data were collected through in-depth interviews, participatory observation, and documentation, then validated through triangulation. The findings reveal that social spirituality is cultivated through ashabiyah khairiyyah (virtue-based social cohesion) emerging naturally within the hidden curriculum. Through moral exemplarity, reflective dialogue, and cross-cultural engagement, Pengajian Malam Ahad serves as a socio-spiritual laboratory (al-‘umran) that transforms individual piety into collective social consciousness.